2013
DOI: 10.1002/bsl.2090
|View full text |Cite
|
Sign up to set email alerts
|

Testing Increases Suggestibility for Narrative‐based Misinformation but Reduces Suggestibility for Question‐based Misinformation

Abstract: A number of recent studies have found that recalling details of an event following its occurrence can increase people's suggestibility to later presented misinformation. However, several other studies have reported the opposite result, whereby earlier retrieval can reduce subsequent eyewitness suggestibility. In the present study, we investigated whether differences in the way misinformation is presented can modulate the effects of testing on suggestibility. Participants watched a video of a robbery and some w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
35
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 56 publications
2
35
1
Order By: Relevance
“…The PET patterns we obtained are the opposite of the frequently reported RES pattern (Chan et al, 2009; 2012; Chan & Langley, 2011; Chan & LaPaglia, 2011; LaPaglia & Chan, 2013; Thomas et al, 2010; Wilford et al, 2014). An important area for future research will be to determine when initial testing is likely to have protective (PET) versus harmful (RES) effects on memory.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The PET patterns we obtained are the opposite of the frequently reported RES pattern (Chan et al, 2009; 2012; Chan & Langley, 2011; Chan & LaPaglia, 2011; LaPaglia & Chan, 2013; Thomas et al, 2010; Wilford et al, 2014). An important area for future research will be to determine when initial testing is likely to have protective (PET) versus harmful (RES) effects on memory.…”
Section: Discussioncontrasting
confidence: 99%
“…However, LaPaglia and Chan (2013) demonstrated that initial testing can produce a PET pattern in this paradigm if misinformation is presented via misleading questions rather than a narrative. Whether initial testing yields a RES pattern or PET pattern may thus be contingent, in part, on how the initial test shapes the learning of subsequent misinformation (Gordon, Thomas, & Bulevich, 2015).…”
mentioning
confidence: 99%
“…Likewise, Pansky and Tenenboim used such an approach whereas we embedded the misinformation into a narrative. This approach has been found to favor test‐enhanced suggestibility (LaPaglia & Chan, 2013), a pattern that was supported by our finding. Another possible reason for the inconsistencies with Pansky and Tenenboim is the diverging operationalization of the types of processing.…”
Section: Discussionsupporting
confidence: 89%
“…This inconsistency may be because of differences in how misinformation was introduced. An inoculation effect of testing against misinformation was more frequently found when misinformation was introduced via questions (LaPaglia & Chan, 2013). Likewise, Pansky and Tenenboim used such an approach whereas we embedded the misinformation into a narrative.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation